A Cooperative’s Governance and Response to Rising Societal Expectations - N. Almarez, David (ASIA PACIFIC JOURNAL OF SOCIAL INNOVATION, 2024)
This is a descriptive case study. It is an evaluation of the corporate governance and corporate citizenship of the MSU-IT Multipurpose Cooperative in relation to its responses to the needs of its members and the community. Data were gathered through surveys. interviews, observations, focus group discussions, and content analysis of documents and were treated both quantitatively and qualitatively. From 38 members and P86.20 initial asset, the MSU-IT MPC grew to more than 30,000 members, more than P400 million in assets, and 103 employees in 32 years. By helping liberate members from usurers and by improving their economic plight, the MSU-IIT MPC provided a model for a self-help initiative for peace building and development. The contribution of the cooperative to the community was made possible by its corporate governance and corporate citizenship. The Board of Directors of the cooperative provided it with strategic guidance, effective risk management, good supervision, effective monitoring, and effective strategies. The cooperative needs a code of ethics and ethical conduct. improved disaster management, and widespread articulation of its core values. The corporate citizenship of the cooperative should be institutionalized and focused on the triple bottom line: people, planet and profit.